Avaliação da sustentabilidade na gestão de resíduos sólidos urbanos dos municípios destinatários ao aterro sanitário compartilhado privado de Mato Grosso : um estudo de caso - Oliveira, Michael Gillbert Silva (2018)
The current paradigm in Urban Solid Waste Management (GRSU) is the challenge of integrated and sustainable management, replacing technical engineering interventions aimed at the implantation of landfills as the main solution, by a concept that strives to find a balance in management , being environmentally efficient, socially acceptable and economically viable. In order to achieve sustainable integrated management and solid waste management, the municipality may have difficulties to carry out these activities, but in general the Brazilian municipalities face many difficulties in the constitution and implementation of a public shared landfill site. The National Policy on Solid Waste proposes, among other objectives, to encourage the decentralization and provision of public services involving solid waste, taking priority in obtaining the incentives established by the Federal Government. The general objective of this work is to evaluate and measure the degree of sustainability of the GRSU of municipalities to the private shared landfill site through a matrix, as well as to verify which type of landfill site management (shared public, shared private and individual) is more interesting for these municipalities. The dissertation was based on a case study in which the exploratory research technique of the eleven municipalities served by the private shared landfill site was worked. For the collection of data and information, we used bibliographical research, documentary, closed questionnaires, geographic positioning software and in loco observation. The sustainability assessments of the municipalities presented the economic, environmental and knowledge dimensions, classified in the range of low sustainability levels. The results of the sustainability level of the GRSU (grouping all dimensions) of the municipalities presented the municipalities of Itanhangá, Lucas do Rio Verde, Nova Mutum, Porto dos Gaúchos and Sorriso classified in the medium sustainability range, and the municipalities of Cláudia, Ipiranga do Norte, Nova Ubiratã, Tapurah and Vera classified as low sustainability. In the analysis of the landfill site management model, the most economical model for all municipalities was the public shared landfill site model presenting a cost of up to 50% less when compared to the models of private or individual shared landfill site.